Arabic research centers what is the object - Lemoui, Dounia; Kabeche, Rabah (Journal of Human Sciences, 2022)
The mental processes of human phenomena give a touch of singularity, which applies to scientific research and which has led to attention to its tools and institutions, to an increasing role for research centres, which are an expression of the transition of scientific research from a phase. "Individual researcher" to the stage of "founding researcher," or in other words collective intellectual work, which supports the skills of the researcher, with the expertise, privileges, tools and relationships offered by the institution, but its place in the Arab world has not been a priority, and its role has not been effective, although it is a strategic partner for which attention has increased globally. This is due to the weakness of the Arab scientific research infrastructure, the lack of awareness and the genuine political will to change in the Arab research centers.